EIS comparative study and critical Equivalent Electrical Circuit (EEC) analysis of the native oxide layer of additive manufactured and wrought 316L stainless steel. (1st May 2020) - Revilla, Reynier I.; Wouters, Benny; Andreatta, Francesco; Lanzutti, Alex; Fedrizzi, Lorenzo; De Graeve, Iris
Highlights: The native oxide layers of SLM and wrought 316L SS were compared using EIS and XPS. XPS analysis showed similar thickness and surface chemistry for both native oxides. The SLM 316L SS showed better barrier properties than the wrought material. The Young modulus proved to be the most appropriate model to fit the EIS results. The results of this work infer structural differences between the native oxide films. Abstract: In this work, a comparative electrochemical impedance spectroscopy (EIS) study of the native oxide layer of selective laser melted and wrought 316L stainless steel is conducted. A careful examination of the data is carried out in order to properly identify the appropriate model to fit the EIS response. From the parameters calculated by fitting the EIS data and a complementary XPS analysis, the electrical and dielectric characteristics of the passive oxide layers of the specimens were obtained. Clear differences were noticed between the two materials, which could definitely contribute to the overall understanding of the corrosion behavior of these materials.